Indonesian Return Migrants Entrepreneurship at Home Village: Knowledge Production and Living Strategy - Paulus Rudolf Yuniarto (Research Centre for Population, Indonesian Institute of Sciences, 2018)
This paper explores the phenomenon of Indonesian return migrant and entrepreneurship issues to their hometown in Malang Regency, East Java. It discusses the linkage between migration experiences and adaption strategies in the economic reintegration of return migrant in home village. By using interviews and observations, the paper concludes some interesting issues. Firstly, the return migrants’ entrepreneurship is the process of accumulating knowledge that acquired before and during migration. Secondly, the return migrants face several challenges including finding appropriate jobs in their villages of origin, including efforts to establish networking with former colleagues and friends as well as difficult to meet their family members’ economic needs. Thirdly, economic reintegration is particularly difficult for the return migrants when their home villages’ infrastructures are not well developed. Four, on the other sides, the return migrants maximize revenues/saving and social remittances for entrepreneurship associated with self-transformation and living strategy at home villages. The return migrants undergo ‘rebirth’ by acquiring new knowledge and occupations, utilizing their economic experiences and mobility, and reintegrating themselves into society both socially and economically. In conclusion, the combination of financial support and social remittance of migrant workers is a valuable asset for economic reintegration of the return migrants.